2020
DOI: 10.15557/jou.2020.0012
|View full text |Cite
|
Sign up to set email alerts
|

Do ankle, hindfoot, and heel ultrasound findings predict the symptomatology and quality of life in rheumatoid arthritis patients?

Abstract: Objectives To evaluate the ankle, hindfoot, and heel changes (determined by physical examination, ultrasound and baropodometry) in patients with rheumatoid arthritis, to compare the findings with healthy subjects, and to analyze if these findings are associated with ankle pain and could affect the quality of life. Methods We enrolled 35 rheumatoid arthritis patients and 35 healthy controls, and evaluated their ankles (tibiotalar joints, tendons), hindfeet (talonavicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…Our findings revealed a statistically significant link between ankle pathologies and higher Health assessment questionnaire and FFI scores. Our findings were consistent with those of Serban et al, 18 Harman and Tekeoğlu, 15 and Jeong et al, 26 who highlighted the association between hindfoot pathologies and functional disability. Our findings differ from those of Petterle et al 27 This may be explained by their examination of only asymptomatic feet, whereas our sample size included both symptomatic and asymptomatic feet.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings revealed a statistically significant link between ankle pathologies and higher Health assessment questionnaire and FFI scores. Our findings were consistent with those of Serban et al, 18 Harman and Tekeoğlu, 15 and Jeong et al, 26 who highlighted the association between hindfoot pathologies and functional disability. Our findings differ from those of Petterle et al 27 This may be explained by their examination of only asymptomatic feet, whereas our sample size included both symptomatic and asymptomatic feet.…”
Section: Discussionsupporting
confidence: 93%
“…At the heel, important sites must be evaluated: the Achilles tendon, retrocalcaneal bursa, as well as the adjacent cortical surface of the calcaneum. 17 Our findings showed the presence of retrocalcaneal bursitis with positive PD, and this matches with Serban et al, 18 who stated that retrocalcaneal bursa had a significant impact on patients' symptomatology and quality of life.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Șerban et al found that the quality of life (QoL) of patients with RA is significantly affected due to ankle and hindfoot pathology, including tibiotalar synovitis, subtalar synovitis, tibialis posterior tenosynovitis/tendinosis, and peroneal tendinosis. Inflammation, as well as degeneration and deformities, were diagnosed [ 6 ]. Tibialis posterior tendon involvement on MRI was frequently observed in those patients with RA presenting with tarsal inflammation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The added value of US in detecting inflammatory lesions [176,179,180] is proven, showing the importance of the method in characterizing disease activity. In the ankle and midfoot, the tibiotarsal (TT) and talonavicular joints are the most frequently affected joints [181][182][183][184] while in the forefoot the metatarsophalangeal (MTP) joints, especially MTP II-V, are most affected [183,185]. Using US, subclinical synovitis was found in 25 % of RA patients in clinical remission [186] and the presence of the power Doppler signal in MTP joints showed predictive value for unstable remission [186] and radiographic progression [187].…”
Section: Ankle and Footmentioning
confidence: 99%